Covalent coupling of high-affinity ligands to the surface of viral vector particles by protein trans-splicing mediates cell type-specific gene transfer. (November 2017) - Muik, Alexander; Reul, Johanna; Friedel, Thorsten; Muth, Anke; Hartmann, Karen Patricia; Schneider, Irene C.; Münch, Robert C.; Buchholz, Christian J.
Abstract: We have established a novel approach for the covalent coupling of large polypeptides to the surface of fully assembled adeno-associated viral gene transfer vector (AAV) particles via split-intein mediated protein- trans -splicing (PTS). This way, we achieved selective gene transfer to distinct cell types. Single-chain variable fragments (scFvs) or designed ankyrin repeat proteins (DARPins), exhibiting high-affinity binding to cell surface receptors selectively expressed on the surface of target cells, were coupled to AAV particles harboring mutations in the capsid proteins which ablate natural receptor usage. Both, the AAV capsid protein VP2 and multiple separately produced targeting ligands recognizing Her2/ neu, EpCAM, CD133 or CD30 were genetically fused with complementary split-intein domains. Optimized coupling conditions led to an effective conjugation of each targeting ligand to the universal AAV capsid and translated into specific gene transfer into target receptor-positive cell types in vitro and in vivo . Interestingly, PTS-based AAVs exhibited significantly less gene transfer into target receptor-negative cells than AAVs displaying the same targeting ligand but coupled genetically. Another important consequence of the PTS technology is the possibility to now display scFvs or other antibody-derived domain formats harboring disulfide-bonds in a functionally active form on the surface of AAV particles. Hence, the custom combination of a universal AAV vector particle and targeting ligands of various formats allows for an unprecedented flexibility in the generation of gene transfer vectors targeted to distinct cell types.